PERILAKU PEMILIH DALAM PILKADA KABUPATEN KUDUS 2013 - Fitriyah, Fitriyah (Politika: Jurnal Ilmu Politik, 2013)
Abstract This study describes of  Kudus Regency (Kabupaten Kudus)  voting behaviour. Voting behavior is explained by three main approaches in the study of voting behavior, which are sociological models, psychological models and rational / economic model. Research was conducted in local election (Pilkada)  Kudus Regency. The research is based on survey with a sample of 100 members who are chosen randomly. The study found that the economic  models and candidate figure are the main factors. Also found that voters had permissive attitude to money politics.   Key words: Perilaku pemilih, Pilkada, politik uang